Analisis Faktor-Faktor Keputusan Pembelian Konsumen Susu Almond di Ralalii Food Yogyakarta - Aurora Yupita Achmada; Nanik Dara Senjawati; Antik Suprihanti (Agrisociabus, 2022)
This study aimed to analyze the effect of motivation, social strata, reference groups, lifestyle, and perceptions to consumer purchase decisions in purchasing almond milk products at Ralalii Food. The research method used a descriptive analysis method with a case study approach. The method of determining respondents used a non-probability sampling method with an incidental sampling approach. Total respondents 100 consumer divided into 50 consumers who purchased and 50 consumers who didn’t purchase Ralalii almond milk. The data used primary data and secondary data. Methods of data collection consists of observation, interviews, and documentation with questionnaires. This study used logistic regression analysis and descriptive analysis. The results showed that lifestyle and consumer perceptions influenced consumers’s purchasing decisions for almond milk products in RalaliiKeywords: Almond Milk, Consumer, Purchase Decisions